Cross-cultural management - Trompenaars, Fons; Melrose Film Productions (Firm) (Brussels : Video Management, 1993)
The programme discuss why management principles lose effectiveness if cultural barriers are crossed
Duplication cannot be made for this tape
Keywords: International business enterprises -- Management -- Social aspects; Corporate culture -- Cross-cultural studies; Communication in management -- Cross-cultural studies